2022
DOI: 10.3390/recycling7020018
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison on Physical and Rheological Properties of Three Different Waste Plastic-Modified Bitumen

Abstract: This study aims to investigate the effect and the possibility of using waste plastic as a sustainable cost-effective polymer to modify bitumen binders. Different types of waste plastic have been used in this modification, including polyethylene terephthalate (PET), high-density polyethylene (HDPE), and low-density polyethylene (LDPE). The modification targets the physical characteristics, rheological properties, and binders’ resistance to ageing. Both long- and short-term ageing are investigated to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Dynamic rheological shear apparatus (AR-2000 N 330) produced by TA Company was adopted. According to the Test Code for Asphalt and Asphalt Mixture of Highway Engineering (JTG E 20-2011), the temperature of three kinds of modified asphalt was scanned [9,10] respectively. The angular frequency is 10 rad/s, the scanning temperature ranges from 58 to 82 ℃, and the scanning interval is 6 ℃.…”
Section: Dynamic Shear Rheometer Test (Dsr)mentioning
confidence: 99%
“…Dynamic rheological shear apparatus (AR-2000 N 330) produced by TA Company was adopted. According to the Test Code for Asphalt and Asphalt Mixture of Highway Engineering (JTG E 20-2011), the temperature of three kinds of modified asphalt was scanned [9,10] respectively. The angular frequency is 10 rad/s, the scanning temperature ranges from 58 to 82 ℃, and the scanning interval is 6 ℃.…”
Section: Dynamic Shear Rheometer Test (Dsr)mentioning
confidence: 99%
“…By partially replacing pure bitumen, PMB offers economical and environmentally friendly paving compared to traditional methods as well [8]. Mashaan et al [9] examined the effects of PET on the physical and rheological properties of bitumen. They concluded that adding PET to bitumen improves its characteristics such as Penetration, Softening Point, and complex shear modulus.…”
Section: Introductionmentioning
confidence: 99%
“…As seen in Figure 1, the phase angle is the angle between the complex modulus and horizontal axis. A large phase angle value indicates that the material possesses more viscous behavior whereas lower phase angle value depicts an elastic behavior [9]. Hence, the determination of G* and δ can illustrate the viscoelastic property of bitumen with regards to rate of loading (time) and temperature [8].…”
Section: Introductionmentioning
confidence: 99%